DEVELOPMENT OF EXPORT POTENTIAL OF UKRAINE'S AGRICULTURAL SECTOR - Nataliia PARKHOMENKO; Iryna OTENKO; Vasyl OTENKO; Marharyta CHEPELIUK (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Given the trends of the economic development, economic crisis, situation of food security, impact of the pandemic Covid-19, it is sensible to research the situation in the agricultural sector in the world and in Ukraine, identify areas for development and assess export potential. These trends indicate the appropriateness and relevance of the study. The aim of the research is to study the state of the agricultural sector of Ukraine and identify areas of development, prospects for development, assessment of export opportunities and export potential. The initial data for the research are obtained on the portal of the State Statistics Service of Ukraine. In the process of research the methods of comparison, analysis, synthesis, generalization, SWOT-analysis are used. The results of the research indicate that Ukrainian enterprises of the agricultural sector are technically equipped, produce high quality products that fit international norms, but concerning the geography of trade of most rural companies, it should be noted a great number of unexplored markets. Moreover, it should be noted that the development of export potential will be facilitated by innovations in the agricultural sector, development of infrastructure in the country, attracting investment.